Treatment of chronic hepatitis B and C in children. (October 2012) - Indolfi, Giuseppe; Nesi, Alessandro; Resti, Massimo
HBV and HCV are the predominant causes of chronic viral hepatitis in children and adults. The main purposes of the present review are to provide the reader with a comprehensive overview of the currently available therapies for chronic hepatitis B and C in children and to critically review the current guidelines and indications for treatment provided by the major international societies and by the consensus of expert panels. Overall, a conservative approach is generally warranted in children with chronic hepatitis B. For HCV, the high effectiveness of pegylated interferon and ribavirin in children with genotype 2 or 3 chronic infection supports the decision to treat. For genotype 1 infection the encouraging results of the use of direct antiviral agents in adults suggest a more conservative approach.